Learning basic physics in Pharmacy Study Program with systems thinking skills needed by pharmacy students - Dhina, Meiry Akmara; Kaniawati, Ida; Yustiana, Yusi Riksa (Momentum: Physics Education Journal, 2024)
This research is a preliminary study aimed at analyzing the methods of teaching basic physics applied in the pharmacy program, as well as its implications for the relevance of physics concepts in pharmacy courses and the development of students' system thinking skills. A cross-sectional survey method was used, employing a structured questionnaire based on the Likert scale, involving physics course instructors from private and public universities. The research findings indicate that, although basic physics has significant potential in contributing to the development of the system thinking skills required by pharmacy graduates, challenges in integrating physics concepts with pharmacy courses still exist. The pharmacy curriculum's focus on pharmaceutical and health aspects may overlook students' understanding of basic physics. Therefore, the importance of developing teaching methods and physics laboratory practices that are appropriate for the pharmacy context becomes clearer. This research concluded that there is a need for the development of more suitable learning methods for basic physics courses in the pharmacy program, with an emphasis on developing system thinking skills crucial in the field of health, and the integration of pharmacy laboratories as a learning support. This is expected to enhance the understanding of physics concepts in the pharmacy context and build relevant system thinking skills for graduates of the pharmacy program.